The Philosophical Foundations, Definitions, and Categories of Human Rights: An International and Islamic Perspective - Muhammad Aslam Rabbani; Dr. Imtiaz Ahmad; Dr Wajid Irshad (Journal of Religion and Society, 2025)
Human nature, intellect, and social evolution have consistently sought principles that ensure the dignity, freedom, equality, and justice of the individual. Although the concept of human rights emerged in modern terminology particularly in Europe during the seventeenth and eighteenth centuries, its roots are deeply embedded in human nature and divine teachings. Greek philosophers, Roman jurists, and later Western thinkers such as John Locke, Jean-Jacques Rousseau, and Thomas Hobbes laid down the philosophical foundations of human rights through rational discourse. In contrast, the Islamic tradition has acknowledged the concept of human rights since its inception, grounding it in divine revelation, prophethood, and the Shariah.The Universal Declaration of Human Rights (1948) by the United Nations presented a global framework in which all individuals were recognized as equal bearers of rights regardless of race, color, religion, or gender. However, the understanding of human rights embodied in this document reflects a particular historical, cultural, and philosophical context—primarily based on secular Western thought. Conversely, in Islamic teachings, human rights are not only viewed as natural but also as divinely bestowed, with their foundations firmly rooted in the Qur’an, the Sunnah, and the era of the Rightly Guided Caliphs. The Cairo Declaration on Human Rights in Islam (1990) introduced this vision within a comprehensive Islamic framework that emphasizes the balance between the individual, society, and the Creator.This paper aims to critically examine the philosophical foundations of human rights from both international and Islamic perspectives, present scholarly definitions, and provide a detailed overview of their various categories. In doing so, it will also highlight the intellectual and practical differences between Western and Islamic conceptions of rights, with the objective of contributing a balanced, inclusive, and academically grounded perspective to the global discourse on human rights. Keywords: Philosophical Foundations, Human Rights, Comprehensive, Framework Islamic Perspective